Situation Report: Bulgaria, 8 July 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Janos Kadar in Bulgaria National Assembly Sessions Ends The New Law on Rents Plenum of the Party CC Todor Zhivkov Reposts on His Visit to Algeria Bulgarian Paper Attacks Nixon Visit to Romania Bulgarian Deputy Foreign Minister in Romania Sino-Bulgarian Trade Agreement for 1969 Signed Miscellaneous Bulgarian-Soviet Tourism Protocol Signed New Bulgarian-Soviet Air Traffic Agreement Signed Jan Piller in Sofia Bulgarian-Hungarian Economic Talks under Way Bulgarian-Moroccan Cultural Co-Operation Bulgarian-Romanian Academic Co-Operation The Mayor of Delhi in Sofia